Alpha‐Synuclein RT‐QuIC in Idiopathic Normal Pressure Hydrocephalus. Issue 6 (28th September 2022) - Fasano, Alfonso; Martinez‐Valbuena, Ivan; Azevedo, Paula; da Silva, Carolina Candeias; Algarni, Musleh; Vasilevskaya, Anna; Anastassiadis, Chloe; Taghdiri, Foad; Kongkham, Paul; Radovanovic, Ivan; Zadeh, Gelareh; Lang, Anthony E.; et al.
Abstract : This study quantified the occurrence of an underlying synucleinopathy in 50 patients with idiopathic normal pressure hydrocephalus by means of real‐time quaking‐induced conversion, a highly sensitive and specific technique capable of detecting and amplifying misfolded aggregated forms of α‐synuclein in the cerebrospinal fluid. Seven patients were positive and they did not differ from negative cases, except for a more frequent L‐dopa responsiveness and gait characterized by a wider base. The two groups did not differ in terms of response rate to tap test or shunt surgery, although step length and gait velocity improved by a lesser extent in positive cases. ANN NEUROL 2022;92:985–991